Microbiological assessment of bile and corresponding antibiotic treatment: a strobe-compliant observational study of 1401 endoscopic retrograde cholangiographies - Rupp, Christian; Bode, Konrad A.; Weiss, Karl Heinz; Rudolph, Gerda; Bergemann, Janine; Klöters-Plachky, Petra; Chahoud, Fadi; Stremmel, Wolfgang; Gotthardt, Daniel; Sauer, Peter (Medicine, 2016)
The aim of this study was to determine the antibiotic susceptibility profiles of bacteria in bile samples and to analyze the clinical relevance of the findings as only limited information about risk factors for elevated frequence of bacterial and fungal strains in routinely collected bile samples has been described so far. - A prospective cohort study at a tertiary care center was conducted. Seven hundred forty-four patients underwent 1401 endoscopic retrograde cholangiographies (ERCs) as indicated by liver transplantation (427/1401), primary sclerosing cholangitis (222/1401), choledocholithiasis only (153/1401), obstruction due to malignancy (366/1401), or other conditions (233/1401). Bile samples for microbiological analysis were obtained in all patients. - The 71.6% (823/1150) samples had a positive microbiological finding, and 57% (840/1491) of the bacterial isolates were gram-positive. The main species were Enterococcus spp (33%; 494/1491) and Escherichia coli (12%; 179/1491). Of the samples, 53.8% had enteric bacteria and 24.7% had Candida spp; both were associated with clinical and laboratory signs of cholangitis (C-reactive proteins 35.0 ± 50.1 vs 44.8 ± 57.6; 34.5 ± 51.2 vs 52.9 ± 59.7; P < 0.001), age, previous endoscopic intervention, and immunosuppression. Multi-resistant (MR) strains were found in 11.3% of all samples and were associated with clinical and laboratory signs of cholangitis, previous intervention, and immunocompromised status. In subgroup analysis, strain-specific antibiotic therapy based on bile sampling was achieved in 56.3% (89/158) of the patients. In cases with a positive bile culture and available blood culture, blood cultures were positive in 29% of cases (36/124), and 94% (34/36) of blood cultures had microbial species identical to the bile cultures. - Bactobilia and fungobilia can usually be detected by routine microbiological sampling, allowing optimized, strain-specific antibiotic treatment. Previous endoscopic intervention, clinical and laboratory signs of cholangitis, and age are independent risk factors. MR bacteria and fungi are an evolving problem in cholangitis, especially in immunocompromised patients.
accepted: December 4, 2015
Gesehen am 27.02.2020